Rapid Purification of Drug Enantiomers using Supercritical Fluid Chromatographic Method: Ibuprofen as a Model Compound - Lee, Hwa Jong; Gahm, Jasper; Jin, Jong Sung; Ahn, Yun Gyong (Indian Journal of Pharmaceutical Education and Research, 2021)
Background: The purification of drug enantiomers is an essential technique because pharmacological activity differs depending on individual enantiomers. Nowadays, supercritical fluid technology is utilized for various purposes in the pharmaceutical field. Methodology: In this study, an efficient and streamlined method development strategy for finding an effective analytical method in supercritical fluid chromatography (SFC) is presented in detail for scaling up to preparative scale and achieving enantiomerically pure product, using ibuprofen as a model compound. Results: Through the optimized preparative method presented, the individual (R) enantiomer of the commercial racemate of ibuprofen can be obtained with a recovery yield of 80.0% and an enantiomeric excess of 95.1 and the individual (S) enantiomer can be obtained with a recovery yield of 77.6% with an enantiomeric excess of 99.3, respectively. Conclusion: The use of analytical and preparative SFC systems has advantages over the conventional chromatography systems in terms of separation time, reduced solvent consumption and high productivity for ibuprofen's enantiomeric purification.
Keywords: Ibuprofen; Analytical supercritical fluid chromatography (Analytic-SFC); Preparative supercritical fluid chromatography (Prep-SFC); Drug; Enantiomer; Purification